2012
DOI: 10.1111/jam.12026
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol potential of phylloplane bacterium Ochrobactrum anthropi BMO-111 against blister blight disease of tea

Abstract: Aims: The present study was carried out to screen the phylloplane bacteria from tea for antagonism against grey blight caused by Pestalotiopsis theae and blister bight caused by Exobasidium vexans and to further evaluate the efficient isolates for disease control potential under field condition. Methods and Results: A total of 316 morphologically different phylloplane bacteria were isolated. Among the antagonists, the isolates designated as BMO-075, BMO-111 and BMO-147 exhibited maximum inhibitory activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…Some endophytic bacteria belonging to Ochrobactrum sp. have been isolated from plants, and these strains exhibit maximum antagonistic activity and possess higher chitinase and glucanase activity (Zhao, Xu, Chang, & Li, ; Zang, Zhao, Liu, & Liang, ; Sowndhararajan, Marimuthu, & Manian, ). Metabolites produced by bacterial species of Ochrobactrum inhibit the growth of a wide range of bacteria and fungi (Han, Peng, & Yi, ; Lebuhn, Achouak, Schloter, & Berge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some endophytic bacteria belonging to Ochrobactrum sp. have been isolated from plants, and these strains exhibit maximum antagonistic activity and possess higher chitinase and glucanase activity (Zhao, Xu, Chang, & Li, ; Zang, Zhao, Liu, & Liang, ; Sowndhararajan, Marimuthu, & Manian, ). Metabolites produced by bacterial species of Ochrobactrum inhibit the growth of a wide range of bacteria and fungi (Han, Peng, & Yi, ; Lebuhn, Achouak, Schloter, & Berge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the isolate effectively decreases the blister blight disease incidence under microplot field experiment (Sowndhararajan et al 2013). Based on the results of physicochemical studies and 16S rDNA analysis, the isolate BMO-111 was identified as O. anthropi and designated as O. anthropi BMO-111.…”
Section: Biocontrol Agent Used In This Studymentioning
confidence: 99%
“…In the experimental field, O. anthropi BMO-111 was reisolated during every plucking round by using leaf washing technique (Sowndhararajan et al 2013). After the isolation, the bacterium was confirmed based on the zone of inhibition against the Pestalotiopsis theae.…”
Section: Reisolation Of O Anthropi Bmo-111mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical pesticide usage is generally accepted as effective strategy, but there is lack of effective chemical product for Fusarium wilt in date palm. Apart from this there are side effects associated with chemical usage (Karlidag et al, 2007;Sowndhararajan et al, 2012;Sathiyabama and Charles, 2015). And also there are acquired resistance in pathogenic bacteria and fungi to commonly used strategies (Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%